Assessment of the Achievement Level Kandri Tourism Village, Gunungpati District, Semarang City - Abhi Kurniawan; Rina Kurniati (Diponegoro University, 2023)
Kandri Tourism Village was founded in 2012, so it has been a tourism village for 9 years. In their development, in 2016 Kandri Tourism Village was classified as a